Snowball Throwing: A Method To Uplift Elementary School Students’ Responsibility on Environment - Framz Hardiansyah (STAI Hubbulwathan Duri, 2022)
The implementation of character education in the current school environment is considered lacking. With these problems, researchers tried to solve the problem by inserting character values into the learning process. Teachers must choose and match character values through the materials to be taught, then apply them to learning. The implementation of character education in the current school environment is considered lacking. With these problems, researchers tried to solve the problem by inserting character values into the learning process. Teachers must choose and match character values through the materials to be taught, then apply them to learning. Snowball throwing is a suitable method for implementing responsibility and environmental care character education. The approach in this research is descriptive qualitative using the percentage formula. Data collection techniques in this study were interviews, questionnaires, and observation. The primary data sources in this study were principals and teachers and were strengthened by student opinions as secondary data sources. The results showed an increase of 3.8% in students' understanding of the character of responsibility and care for the environment after using the snowball throwing method, with 82% in the excellent category.